Experimental Research on Optimization Extruder Process Parameters for Pineapple Pomace-Based Fish Feed - Oluwafemi Babatunde Oduntan; Adeleke Isaac Bamgboye; Abosede Oluwakemi Oduntan (Jurnal Keteknikan Pertanian Tropis dan Biosistem, 2022)
A single screw water-cooled jacketed extruder has been proposed to produce the fruit waste extrusion process of fish feed because of its superficial characteristics. This research mainly examined the effects of various extrusion conditions: feeding rate, screw speed, feed moisture, barrel temperature, cutting speed, and die open surface area. While maintaining the feed specifications (38% proteins and 5% lipids), four formulations with different pomace inclusions were obtained. The processing methodologies (with mash moisture and varied extruder parameters) were then based on three fundamental aspects (machine torque, apparent viscosity, and efficiency). They were studied using Response Surface Methodology (RSM). The influence of screw speed, moisture, and pomace inclusion was most significant. Optimum extrusion conditions were found at a feed rate of 1.47 kg.min-1, screw speed of 356.44 rpm, humidity of 16.04%, temperature of 60 °C, cutting speed of 1300 rpm, pomace inclusion rate of 10.59%, and an open surface die obtained 88.63%. The maximum desirable value of 0.61 resulted in 444.16 Nm-1 torque, 1008.98 Pa-s apparent speed, and 75.21% efficiency. The extruder evaluation demonstrated remarkable performance in producing pineapple pomace extrudates without impeding machine operating principles, redefining the robustness of extrusion process factors and their interactions in the process state.